MATHEMATICAL SUBSTANTIATION OF THE INTERACTION OF THE TUBE WITH THE BOTTLE CONVEYOR OF THE POTATO PLANTER - MYZYUK, Andrii (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The planting machines of the manufactured potato planters are mostly not in fully comply with agrotechnical requirements. Based on the analysis modern designs of planting machines, a conclusion was made about the advantages and shortcomings of existing designs of potato planters. The big disadvantage that especially affects crop yields, is low uniformity distribution of potato tubers along the length of the row, as well as the depth of planting. Wherein deterioration in the distribution of potato tubers occurs mainly at the time ejection of potatoes to the bottom of the furrow due to the rolling of tubers along its bottom. Big impact on fit quality potatoes by mechanization provides uniform distribution potatoes along the bottom of the furrow. Sustainable disallocation of tubers when planting existing significantly affects the crop yield, because in this case, the feeding area is formed niya for growing potatoes. Compliance even distribution of seed material is a priority when designing planters. Modern planting machines are far from being fully compatible with imposed agrotechnical requirements for the distribution of planting material.Analyzing the technological processes of potato planters, it can be argued that the spoon-conveyor planter in comparison with the revolving planter provides less injury to potato tubers because contact occurs at the time of laying the tubers on spoons and when falling to the bottom of the hole . Whereas in the revolver the height and rate of fall are higher.The analysis of dependence showed that with increasing the speed of the potato planter to 6.2 m / s injury of tubers increases from 15 to 31%. The study shows that when changing the speed of the conveyor from 0.4 to 1.8 m / s there is an increase in the gaps of tubers in the furrow (up to 3%; 2.4%; 2.2% at a step of 0.25 m; 0, 32 m and 0.4 m), ie. spoons cease to capture them steadily from the bucket.
Keywords: conveyor; potatoes; tubers; pickling; planting